Research progress of auricular acupoint stickingin the treatment of insomnia in the elderly (耳穴贴压治疗老年失眠患者的研究进展) - CHEN Li (陈丽); XIE Wei (谢薇); REN Xiuya (任秀亚); ZHAO Lingling (赵玲玲); XIANG Yiming (向毅明); ZHOU Yihan (周艺涵); LUO Liyuan (罗丽媛); LIU Xing (刘兴); SHAO Shuai (邵帅) (Association of Integrative Nursing, 2023)
In this paper, the application of auricular acupoint sticking in elderly patients with insomnia in the past 5 years was reviewed, for better understanding the status quo of auricular acupoint sticking in the treatment of insomnia in the elderly. The application of auricular acupoint sticking therapy was summarized, in order to provide some ideas and reference for elderly patients with insomnia in clinical application. (睡眠障碍是影响老年患者生活质量的常见疾病。本研究就近年来耳穴贴压在老年失眠患者中的临床研究进行归纳, 对老年失眠患者的耳穴贴压疗法进行概述, 旨在为临床治疗老年失眠患者提供思路及参考。)